The identification of patient‐specific mutations reveals dual pathway activation in most patients with melanoma and activated receptor tyrosine kinases in BRAF/NRAS wild‐type melanomas. Issue 4 (18th December 2018) - Appenzeller, Silke; Gesierich, Anja; Thiem, Alexander; Hufnagel, Anita; Jessen, Christina; Kneitz, Hermann; Regensburger, Martina; Schmidt, Cornelia; Zirkenbach, Vanessa; Bischler, Thorsten; Schilling, Bastian; Siedel, Claudia; et al.
Abstract : Background: Increasing knowledge of cancer genomes has triggered the development of specific targeted inhibitors, thus providing a valuable therapeutic pool. Methods: In this report, the authors analyze the presence of targetable alterations in 136 tumor samples from 92 patients with melanoma using a comprehensive approach based on targeted DNA sequencing and supported by RNA and protein analysis. Three topics of high clinical relevance are addressed: the identification of rare, activating alterations; the detection of patient‐specific, co‐occurring single nucleotide variants (SNVs) and copy number variations (CNVs) in parallel pathways; and the presence of cancer‐relevant germline mutations. Results: The analysis of patient‐matched blood and tumor samples was done with a custom‐designed gene panel that was enriched for genes from clinically targetable pathways. To detect alterations with high therapeutic relevance for patients with unknown driver mutations, genes that are untypical for melanoma also were included. Among all patients, CNVs were identified in one‐third of samples and contained amplifications of druggable kinases, such as CDK4, ERBB2, and KIT. Considering SNVs and CNVs, 60% of patients with metastases exhibited co‐occurring activations of at least 2 pathways, thus providing a rationale for individualized combination therapies. Unexpectedly, 9% of patients carry potentially protumorigenic germline mutations frequently affecting receptor tyrosine kinases. Remarkably two‐thirds of BRAF/NRAS wild‐type melanomas harbor activating mutations or CNVs in receptor tyrosine kinases. Conclusions: The results indicate that the integrated analysis of SNVs, CNVs, and germline mutations reveals new druggable targets for combination tumor therapy. Abstract : The presence of targetable alterations in 136 tumor samples from 92 patients with melanoma is analyzed using a comprehensive approach based on targeted DNA sequencing and supported by RNA and protein analyses. The integrated analysis of single nucleotide variants, copy number variations, and germline mutations reveals new druggable targets for combination tumor therapy.